Angiogenesis is Inhibited by Arsenic Trioxide Through Downregulation of the CircHIPK3/miR-149-5p/FOXO1/VEGF Functional Module in Rheumatoid Arthritis - Zhang, Juan; Ma, Yeye; Zhang, Yue; Niu, Sijia; Chu, Maolin; Zhang, Zhiyi (Frontiers in Pharmacology, 2021)
Angiogenesis is crucial in the pathogenesis of rheumatoid arthritis (RA). Arsenic trioxide (ATO) has been reported to inhibit synovial angiogenesis via VEGF-centered functional module. However, the exact mechanisms remain unclear. Circular RNAs (circRNAs) are emerging as important regulators in RA, and the detailed mechanisms remain largely unknown. Here, we reported a circRNA (circHIPK3), which was significantly increased in RA fibroblast-like synoviocytes (RA-FLS) after TNF-α induction. Moreover, VEGF content in RA-FLS and human dermal microvascular endothelial cells (HDMECs) co-culture and VEGF-induced endothelial vascularity were significantly elevated in accordance with circHIPK3 levels. CircHIPK3 was further illustrated to be a sponge for the FOXO1-targeting miR-149-5p, leading to the changing expression of VEGF. These networked factors mainly form a functional module regulating angiogenesis in RA-FLS and the expression of this functional mudule could be significantly downregulated by ATO with consistently reduced vascularity in vitro. In the collagen-induced arthritis (CIA) mice model, ATO or intra-articular injection adeno-associated-virus-si-circHIPK3 was demonstrated to alleviate synovial VEGF expression plus arthritis severity respectively. Thus we elucidate a previously-unknown mechanism between circRNAs and RA, and ATO has a significant protective effect via inhibition of circHIPK3/miR-149-5p/FOXO1/VEGF functional module, suggesting a great potential for combination therapy of ATO with circHIPK3 silencing.